Loss of IL1RA promotes prostate cancer growth and metastasis by activating Akt signaling pathway - Cheng Zhang; Junjie Yu; Taoze Ji; Kai Zhao; Mingquan Chen (PLoS ONE, 2026)
Background. Interleukin-1 receptor antagonist (IL1RA) blocks the interaction between IL-1 and its receptors. It modulates inflammatory responses, cell proliferation, and the invasion of cancer cells. In this study, we examined the biological functions of IL1RA and the mechanisms that influence its effects on prostate cancer (PCa). Materials and methods. We performed RT-qPCR and Western blot analyses to evaluate IL1RA expression levels in various cell lines. For functional studies, we employed MTT, colony formation, soft agar, wound healing, and transwell migration and invasion assays. Then, we analyzed Western blots to elucidate the underlying mechanisms involved. Xenograft mouse models were ultimately established after the overexpression of IL1RA. Results. IL1RA was expressed at higher levels in prostate epithelial cells compared with the PCa cell lines. BPH cells with lower IL1RA expression exhibited an increased cell proliferation. The PCa cell lines C4-2B and LNCap, which overexpressed IL1RA, demonstrated suppressed tumorigenic properties in vitro. The in vivo experiment demonstrated an inhibitory effect on tumor growth in xenograft mice. Furthermore, Western blot results indicated elevated phosphorylated AKT levels in BPH cells with IL1RA knockdown, and phosphorylated AKT and GSK-3 β levels were reduced in C4-2B and LNCap cells that overexpressed IL1RA. Conclusion. This study revealed that IL1RA low expression is associated with PCa progression. Our finding has great clinical and translational significance. The potential clinical application of IL1RA as a therapeutic target for PCa requires further investigation.